Expanding Fields of Architectural Discourse and Practice Curated Works from the P.E.A.R. Journal - Butcher, Matthew; O'Shea, Megan (UCL Press, 2020)
Expanding Fields of Architectural Discourse and Practice presents a selection of essays, architectural experiments and works that explore the diversity within the fields of contemporary architectural practice and discourse. Specific in this selection is the question of how and why architecture can and should manifest in a critical and reflective capacity, as well as to examine how the discipline currently resonates with contemporary art practice. It does so by reflecting on the first 10 years of the architectural journal, P.E.A.R. (2009 to 2019). The volume argues that the initial aims of the journal - to explore and celebrate the myriad forms through which architecture can exist - are now more relevant than ever to contemporary architectural discourse and practice. Included in the volume are architectural practitioners, design researchers, artists, architectural theorists, historians, journalists, curators and a paleobiologist, all of whom contributed to the first seven issues of the journal. Here, they provide a unique presentation of architectural discourse and practice that seeks to test new ground while forming distinct relationships to recent, and more longstanding, historical legacies.